Al Ghazzali’s philosophy of knowledge: a comprehensive guideline and solutions to promote Islamic education in human life - Afridi, Muhammad Adil Khan (2012)

(untitled)
There have been many sects throughout Islamic antiquity. To be contingent on an intellectual or sect as the basis for inaugurating a base for learning is deceptive. Other intellectuals and sects need to be deliberated as well. This development need consequently comprises an inclusive investigation of a variety of key suppliers to Islamic teachings during the course of history. Al-Ghazzali’s been very specifically about education and suggested an integral part of the Islamic educational model. Thus, this model is the key link in the Master-Pupil and Parent-Child relationships. Since motherhood is an integral part of the family unit, this study contains a re-examination of women’s education from AI-Ghazzali’s point of view, because some claim that, Muslim women are being oppressed or not at all reinvigorated to become fully educated. AI-Ghazzali’s legacy holds the beginnings of several influential concepts that can be useful to modern concepts of Islamization of Knowledge. The quest of knowledge was AI-Ghazzali’s main importance, one that he deliberated to be among the highest forms of worship. AI-Ghazzali’s philosophy of knowledge thoroughly conveyed a chain of unified methods for achieving such knowledge. He discussed the role of the intelligence, the way of knowing, the learning process, and the obstacles to the learning process. This is his legacy. AI-Ghazzali’s philosophy resembles the importance, engaged by Islam on religious and spiritual aspect of life, which is fundamental to the structure of a Muslim.